Universitas Islam Negeri (Studi Historisitas, Perkembangan dan Model Integrasi Keilmuan) - Rahmat Rifai Lubis (Hikmah, 2021)
This study aims to analyze the historicity, development and model of curriculum integration at the State Islamic University. This research is a qualitative research with a literature study approach. The results of the study explain that UIN is a transformation from IAIN which was first established in 2002. The change from IAIN to UIN has three stages, namely: (1) the Pioneering and exploratory stages which were carried out during Harun Nasution's time as Chancellor, (2) Continuation and maturation stages. concept, this stage occurred during the time of Quraish Shihab as rector, at this stage a proposal for changing IAIN to UIN was prepared which was led by Azyumardi Azra (3) The stage of maturation of ideas and implementation. Since 2002 (the first establishment of UIN) until now the development of UIN has progressed very rapidly. In terms of quantity, currently there are 23 UINs out of a total of 58 PTKIN or around 40% of the total existing Islamic universities. The scientific integration model at UIN Syarif Hidayatullah is the reintegration of knowledge, UIN Sunan Ampel Surabaya has the concept of integrated twin towers (ITT), UIN North Sumatra carries the Wahdatul Ulu concept, UIN Sunan Kalijaga has the concept of Interconnection Integration